2019
DOI: 10.1364/oe.27.015485
|View full text |Cite
|
Sign up to set email alerts
|

Flat liquid jet as a highly efficient source of terahertz radiation

Abstract: Polar liquids are strong absorbers of electromagnetic waves in the terahertz range, therefore, historically such liquids have not been considered as good candidates for terahertz sources. However, flowing liquid medium has explicit advantages, such as a higher damage threshold compared to solid-state sources and more efficient ionization process compared to gases. Here we report systematic study of efficient generation of terahertz radiation in flat liquid jets under sub-picosecond single-color optical excitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 40 publications
(31 reference statements)
0
32
0
2
Order By: Relevance
“…Figure 2(b) demonstrates the THz waves energy dependence on the temporal delay ∆τ between two pump pulses typical for the series of our experiments on THz generation in water jet of 100 and 270 µm thickness. Figure 2(b) shows that the maximum enhancement value corresponds to the optimal duration for a certain jet thickness [9]. Moreover, using a thicker jet we get weaker THz signal due to the linear THz absorption in water medium.…”
Section: Thz Radiation Energy Enhancement In Flat Water Jetsmentioning
confidence: 90%
See 1 more Smart Citation
“…Figure 2(b) demonstrates the THz waves energy dependence on the temporal delay ∆τ between two pump pulses typical for the series of our experiments on THz generation in water jet of 100 and 270 µm thickness. Figure 2(b) shows that the maximum enhancement value corresponds to the optimal duration for a certain jet thickness [9]. Moreover, using a thicker jet we get weaker THz signal due to the linear THz absorption in water medium.…”
Section: Thz Radiation Energy Enhancement In Flat Water Jetsmentioning
confidence: 90%
“…The phenomenon of the generation of THz radiation in liquid media has been rather fully considered in works [6,8]. The single-color excitation of acetone jet in the recent paper [9] gave an optical-to-terahertz conversion efficiency value comparable to the case of two-color laser filamentation in atmospheric air. Moreover, the authors of [10] have successfully modified the experimental setup replacing the flat liquid jets by liquid columns, thus, increasing THz generation efficiency by an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…[149] A theoretical parametric study as a function of the driving laser wavelength, from the near to the far infrared, [150] as well as an experimental one up to 2.6 µm, [151] confirms that the use of long wavelength short pulses, above critical power, results in energetic THz pulses. One way is to limit the propagation effects by confining the liquid in space, like in the case of water films [154] or water lines. [148] The THz radiation generated by a two-color plasma filament has a conical emission pattern, a feature characteristic especially for long filaments.…”
Section: Thz Sources Based On Laser-filament-induced Plasmasmentioning
confidence: 99%
“…Considering the damage issue in solid samples, liquids can be an ideal target for plasma-based THz wave emission since it can be refreshed continuously during experiments. Indeed, experiments with a water film [25][26][27][28][29] or a line [30] and other liquids such as deionized-water, alcohols, acetone, dichloroethane, or carbon disulfide [31] have been carried out. It is also reported that THz wave emission can be induced in association with X-ray emission from thin water flow and its intensity is enhanced under double-pulse excitation [32].…”
Section: Introductionmentioning
confidence: 99%